2013
DOI: 10.4081/ejh.2013.e12
|View full text |Cite
|
Sign up to set email alerts
|

An ex vivo study on immunohistochemical localization of MMP-7 and MMP-9 in temporomandibular joint discs with internal derangement

Abstract: Internal derangement (ID) is among the most common disorders of the temporomandibular joint (TMJ). Previous research by our group highlighted a correlation between apoptosis and TMJ ID. Metalloproteinases (MMP)-7 and -9 have been shown to play an important role in extracellular matrix ECM) homeostasis and, through it, in joint disc remodelling. The immunohistochemical expression of MMP-7 and -9 was investigated in discs from patients with TMJ ID and from healthy donors and compared with the degree of histologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 44 publications
0
49
0
Order By: Relevance
“…For the past few years, many papers have been published showing the participation of various markers and distinct pathways in the progression of TMJ ID using TMJ discs and synovial fluid (Kubota et al, 1998, De Alcantara Camejo et al, 2014, Loreto et al, 2013, Wake et al, 2013, Kim et al, 2012, Leonardi et al, 2010a, Vernal et al, 2008, Sato et al, 2003. Sato et al, in 2003, performed a study using also an immuno-histochemical technique for the examination of synovial tissue from 46 temporomandibular joints with internal derangement in 44 patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the past few years, many papers have been published showing the participation of various markers and distinct pathways in the progression of TMJ ID using TMJ discs and synovial fluid (Kubota et al, 1998, De Alcantara Camejo et al, 2014, Loreto et al, 2013, Wake et al, 2013, Kim et al, 2012, Leonardi et al, 2010a, Vernal et al, 2008, Sato et al, 2003. Sato et al, in 2003, performed a study using also an immuno-histochemical technique for the examination of synovial tissue from 46 temporomandibular joints with internal derangement in 44 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory changes in the TMJ modify physical and functional properties, first reversibly and finally irreversibly, reducing its ability to withstand pressure and compression forces (Israel et al, 1991). Loreto et al (2013). showed that MMP-7 and MMP-9 are expressed in arthritic joints, and provided evidence of a role for those MMPs in disc damage in TMJ ID, with higher expression detected in the posterior band rather than in the anterior and intermediate bands of ADDwR and ADDwoR discs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…caries lesion), 23 even though the level of TIMPs found in active carious lesions is insufficient to block the progression of dental hard tissue destruction mediated by MMPs. 24 Cysteine cathepsin found in dentine has the ability to activate latent MMPs. 25 The cathepsin activity increases with increasing depth of lesion.…”
Section: Role Of Mmps In Dental Cariesmentioning
confidence: 99%
“…For immunohistochemical analysis, specimens were processed as previously described [26]. Briefly, the slides were dewaxed in xylene, hydrated using graded ethanols and were incubated for 30 min in 0.3% H 2 O 2 /methanol to quench endogenous peroxidase activity and then rinsed for 20 min with phosphate- Xels of the analyzed fields.…”
Section: Immunohistochemistry (Ihc)mentioning
confidence: 99%